Intermedia Agenda-Setting on Pansela: A Corpus Linguistics Analysis of Government and Public Agendas (2016 – 2024) - Nuri Shabrina (Jurnal Komunikasi dan Bisnis, 2025)
The South Coast Route (Pansela) is one of the government’s strategic infrastructure projects promoted through various digital channels, including press releases and social media. Despite ongoing campaigns, the route remains underutilized. This study aims to explore the relationship between government media (press releases) and public responses on Instagram regarding Pansela route, as well as to identify the agenda gaps using the Intermedia Agenda-Setting Theory. The method employed is corpus linguistics, which categorizes words into five key topics, followed by a Spearman correlation test to measure the relationship between the government agenda and the public agenda. The findings reveal no significant correlation between the two agendas. The government agenda emphasizes infrastructure progress, policy, and tourism development, while the public agenda highlights comparisons between Pansela, Pantura, and toll roads, as well as concerns over inadequate road conditions. These findings indicate that the government's persuasive messages were not fully accepted by the public who tend to respond based on their experiences. Theoretically, this study extends the Intermedia Agenda-Setting framework to institutional and public interactions, while practically, it offers insights to the government for improving participatory digital communication strategy to bridge agenda gaps in digital campaigns.